'Green spirituality' : towards an ecological ethic in theological reflection and praxis - Becker, Francine (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Religion and Culture) (Practical Theology and Missiology))--University of Stellenbosch, 2010.